Mapping of the breakpoints on the short arm of chromosome 17 in neoplasms with an i(17q) - Scheurlen, Wolfram; Schwabe, Georg C.; Seranski, Peter; Joos, Stefan; Harbott, Jochen; Heydemann-Metzke, Simone; Döhner, Hartmut; Poustka, Annemarie; Wilgenbus, Klaus; Haas, Oskar A. (Genes, chromosomes & cancer, 1999)
Isochromosomes are monocentric or dicentric chromosomes with homologous arms that are attached in a reverse configuration as mirror images. With an incidence of 3-4%, the i(17q) represents the most frequent isochromosome in human cancer. It is found in a variety of tumors, particularly in blast crisis of chronic myeloid leukemia (CML-BC), acute myeloid leukemia (AML), non-Hodgkin's lymphoma (NHL), and medulloblastoma (MB), and indicates a poor prognosis. To determine the breakpoints on the molecular genetic level, we analyzed 18 neoplasms (six CML, four AML, one NHL, and seven MB) with an i(17q) and two MB with a pure del(17p) applying fluorescence in situ hybridization (FISH) with yeast artificial chromosome (YAC) clones, P1-artificial chromosome (PAC) clones, and cosmids from a well-characterized contig covering more than 6 Mb of genomic DNA. We identified four different breakpoint cluster regions. One is located close to or within the centromere of chromosome 17 and a second in the Charcot-Marie-Tooth (CMT1A) region at 17(p11.2). A third breakpoint was found telomeric to the CMT1A region. The fourth, most common breakpoint was detected in MB, AML, and in CML-BC specimens and was bordered by two adjacent cosmid clones (clones D14149 and M0140) within the Smith-Magenis syndrome (SMS) region. These results indicate that the low copy number repeat gene clusters which are present in the CMT and SMS regions may be one of the factors for the increased instability that may trigger the formation of an i(17q). Genes Chromosomes Cancer 25:230-240, 1999. © 1999 Wiley-Liss, Inc.